Boosting the photoreduction activity of Cr(vi) in metal–organic frameworks by photosensitiser incorporation and framework ionization. Issue 33 (11th August 2020) - Zheng, He-Qi; He, Xing-Hao; Zeng, Yong-Nian; Qiu, Wei-Hua; Chen, Jin; Cao, Gao-Juan; Lin, Rong-Guang; Lin, Zu-Jin; Chen, Banglin
Abstract : The Cr(VI) photoreduction efficiency in a Zr-based MOF is largely boosted by photosensitizer introduction and framework ionization, resulting from the great improvement of both the visible light harvesting ability and Cr(vi ) adsorption performance. Abstract : It is mandatory to decontaminate Cr(vi ) species from water streams due to their high toxicity. The photoreduction of hazardous Cr(vi ) to nontoxic Cr(iii ) is a very promising approach to control Cr(vi ) pollution. Although some MOFs and their composites have been employed as photocatalysts to reduce toxic Cr(vi ), their catalytic activities are always limited by inefficient visible light absorption and inferior Cr(vi ) adsorption performances. Herein, cationic Ru-UiO-dmbpy(1) that is decorated with a high density of cationic charges and also embedded with catalytically competent and visible light harvesting moieties ( i.e. Ru(bpy)3 ) was successfully synthesized by a sequential mix-and-match and ionization process. The presence of Ru(bpy)3 moieties makes Ru-UiO-dmbpy(1) an excellent visible-light harvester, extending the absorption edge from 420 nm for pristine UiO-bpy to about 780 nm for Ru-UiO-bpy/Ru-UiO-dmbpy(1). Driven by ion exchange, Ru-UiO-dmbpy(1) shows a large adsorption rate constant ( k 2 ) of 1.33 × 10 −2 g mg −1 min −1 in the adsorption of Cr2 O7 2−, which is 8.26 times that of pristine UiO-bpy and 6.27 times that of the non-ionization counterpart Ru-UiO-bpy(1) under the same adsorption conditions. The equilibrium Cr2 O7 2− uptake capacity of Ru-UiO-dmbpy(1) reaches 101.8 mg g −1, which is about 1.98 and 1.81 times that of UiO-bpy and Ru-UiO-bpy(1), respectively. With an efficient visible light absorption ability and superior Cr(vi ) adsorption performance, Ru-UiO-dmbpy(1) shows a reaction rate constant ( k 1 ) of 0.011 min −1 in the photoreduction of Cr(vi ) without any sacrificial agents under visible light illumination, which is much larger than those of pristine UiO-bpy (0.003 min −1 ) and its non-ionization counterpart Ru-UiO-bpy(1) (0.007 min −1 ) under the same conditions. The result unambiguously demonstrates that the Cr(vi ) photoreduction activity could be largely enhanced by photosensitiser introduction and framework ionization. To further evaluate the catalytic performance of Ru-UiO-dmbpy(1), Cr(vi ) reduction was also investigated in the presence of various sacrificial agents. Remarkably, a high Cr(vi ) photoreduction rate of 6.4 mgCr(VI) gcatalyst −1 min −1 was obtained when benzyl alcohol was used as a sacrificial agent, which is a record value among those reported for MOF-based photocatalysts.